The Effective British Broadcasting Corporation’s (BBC) Optimal Pronunciation Vocational School's (OPVS) Podcast - Susanti, Rr Retno Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The objective of this initiative is to improve pronunciation fluency in vocational schools by including a British accent. This study utilized the Wilcoxon signed-rank test as a component to collect both quantitative and qualitative data on product moment SPSS. The data was acquired by pronunciation evaluation test and analysis questions. The data employed in this study was gathered from a vocational school consisting of thirty students enrolled in a hospitality industry and cooking programme. The mean test score is 8.00, and the total amount of ranks is 120.00. According to the statistical test output provided, it is referred to as Asymp. The p-value (two-tailed) is 0.001. Based on the test statistics output above, it is known that Asymp. Sig. (2-tailed) has a value of 0.001, because the value of 0.001 is smaller than 0.05, it can be concluded there is a difference between learning outcomes using text transcripts and shadowing BBC Podcasts and those that do not use text transcripts and shadowing BBC Podcasts. The podcast produced by the BBC can enhance language acquisition by improving pronunciation skills, stimulating students' motivation to achieve English competence, and assisting listeners in developing a predominantly British accent